Editorial - K. C., Bed Raj (Voice: A Biannual & Bilingual Journal, 2025)
We are delighted to present Voice: A Biannual and Bilingual Journal, Volume 17, Number 1, July 2025, published by the Autar Dei Chaudharain Research Centre (ADCRC) at Mahendra Multiple Campus, Nepalgunj, Banke, Nepal. This issue comprises sixteen scholarly articles, twelve in English and four in Nepali. Collectively, they represent a wide spectrum of disciplines, ranging from social sciences and education to literature, natural sciences and management. By bringing together such a variety of perspectives, this volume continues the journal’s tradition of promoting bilingual and interdisciplinary academic dialogue. The contributions in this edition reflect pressing contemporary concerns as well as enduring scholarly questions. Some articles examine policy, economy and governance, highlighting challenges and opportunities in national development. Others focus on society and culture, offering reflections on shifting traditions, linguistic practices and evolving modes of communication. In the fields of education and management, the research sheds light on classroom practices, organizational behavior and broader institutional frameworks. Equally significant are studies in natural sciences, which broaden our understanding of biodiversity and ecological change. Together, these contributions not only add to academic knowledge but also encourage readers to think critically about Nepal’s ongoing transformations in a global context. As a bilingual journal, Voice seeks to create a bridge between Nepali and English scholarship. The inclusion of articles in both languages provides a platform for researchers to engage with diverse audiences while preserving cultural and linguistic richness. This dual approach helps ensure that academic insights remain accessible to a broad community of readers, strengthening the exchange of ideas across linguistic and disciplinary boundaries. We sincerely acknowledge the invaluable efforts of our contributors, reviewers and the editorial team, whose dedication has made this publication possible. Their commitment to maintaining high academic standards ensures the continued growth and recognition of Voice. We also thank our readers for their ongoing encouragement and support. With this issue, we reaffirm our commitment to fostering critical inquiry, nurturing intellectual collaboration and sustaining a vibrant platform for scholarly exchange